A Multimodal Thematic Teaching Material Application for Supporting Blended Learning In Elementary Education - Mansur, Mansur; Setyaningrum, Saumi; Kartini, Kartini; Mahrani, Mahrani; Setyaningrum, Vidya (The Magister of Islamic Education IAIN Pontianak, 2024)
This research is motivated by the conditions in the field where so far the teacher teaches still using printed teaching materials, and other separate learning resources that must be prepared in advance and are not yet available in the package books used so that the teaching materials are less practical and complete, related to this condition, the researcher aims to develop a Multi Modal Teaching Material Application Product with the object of developing Thematic Teaching Materials in grade 5 Elementary School / Madrasah Ibtidaiyah. The method used is the R&D model with 4D steps according to Tagarajan. Starting from the stages of defining, designing, developing, and distributing products. But in this study it is only limited to producing products only (Product Validation) the next stage is carried out in the next study. The techniques used include discussions with experts on product design, distributing Product Validation questionnaires. The data obtained were then analyzed using qualitative and quantitative approaches. The results showed that multimodal teaching materials were developed by involving 8 PGMI students. Products validated by experts, consisting of 8 media experts and learning material experts. The results showed data Validation of product feasibility of 3.94 or 98.2% with a very feasible category. Product feasibility validation data from the media aspect shows 3.97 or 99% with a very feasible category. Product feasibility validation data from the material content aspect shows a value of 3.94 or 98.5%, a value indicating that the material in this application is very feasible. So it can be concluded that the multimodal teaching materials developed have a level of feasibility as a product Multimodal teaching materials show very feasible results as Multimodal Thematic Teaching Material Applications and can be continued in the next research hold from the R & D ledge Test practicality and effectiveness in limited and widespread fields to then be distributed as Teaching Materials in the field